2016
DOI: 10.1007/s11695-016-2397-4
|View full text |Cite
|
Sign up to set email alerts
|

Banded Gastric Bypass: Better Long-Term Results? A Cohort Study with Minimum 5-Year Follow-Up

Abstract: BackgroundWhile gastric bypass has been the treatment of choice for morbid obesity, insufficient weight loss and even weight regain has been observed in a sub-group of patients. Dilatation of the pouch, pouch outlet, and proximal alimentary limb have been suggested to cause weight regain on the long term. The banded gastric bypass surgery has been introduced to overcome this problem.MethodsFour hundred thirty-two patients (n = 254, non-banded/n = 178, banded-GaBP Ring™) were followed-up for 5 years. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 27 publications
1
40
0
3
Order By: Relevance
“…This difference in weight loss was maintained in all follow-up visits starting at the 6-month interval ( Table 2 and Reports comparing OAGB to RYGB have reported at least equal or more %EBWL. 16,26 Similarly, the weight loss outcome in the BGBP group in this study is similar to what has been reported by Bessler et al and other authors 10,28,29 who have shown better and sustained weight loss outcomes after BGBP compared to RYGB.…”
Section: Discussionsupporting
confidence: 91%
“…This difference in weight loss was maintained in all follow-up visits starting at the 6-month interval ( Table 2 and Reports comparing OAGB to RYGB have reported at least equal or more %EBWL. 16,26 Similarly, the weight loss outcome in the BGBP group in this study is similar to what has been reported by Bessler et al and other authors 10,28,29 who have shown better and sustained weight loss outcomes after BGBP compared to RYGB.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, the incidence of food intolerance appears to be higher among individuals who underwent banded bypass. Nonetheless, the current reported results in the literature are mixed, with a number studies showing a significantly higher weight loss, and others demonstrating no advantages (8,9) . The impact of the placement of bands on the outcomes after OAGB remains not completely determined and, to date and according to our knowledge, two studies performed at the same centre and published by Clarke et al and Sheikh et al described this possibility; these authors reported significant weight loss and resolution of co-morbidities (10,11) .…”
Section: Early Weight Loss Outcomes and Glucose Metabolism Parametersmentioning
confidence: 89%
“…Обоснованность подобного способа решения проблемы опирается на результаты сравнительных клинических исследований отдаленных результатов шунтирования желудка с дополнительной установкой бандажа (нерегулируемого) и без него. Применение препятствующего дилатации «малого» желудка полимерного кольца позволяет достичь достоверно большей эффективности снижения и контроля избыточной массы тела в отдаленном периоде (10 и более лет после операции): 81,7 против 62,3 % [11,16].…”
Section: же лудочное шунтирование Roux-en-yunclassified
“…Во время операции проводили его частичное заполнение. Регулировка бандажа осуществляется по тем же принципам, что и при первичной имплантации устройства [16].…”
Section: же лудочное шунтирование Roux-en-yunclassified
See 1 more Smart Citation